Taylorism, Fordism and Toyotism - Ribeiro, Andressa de Freitas (Pontifícia Universidade Católica de São Paulo, 2015)
This article presents a brief discussion on the similarities and differences between the production patterns known as Taylorism, Fordism and Toyotism. The methodology involves bibliographic research. These three production patterns characterize the development of capitalism from the end of the 19th century through today. What are the main characteristics of these production patterns? What modifications occur in the dynamics of capitalism with the passage from one pattern to the next?